INNOVATIVE APPROACHES TO CREATIVITY DEVELOPMENT THROUGH BIONICS IN PRESCHOOL EDUCATION (International journal of artificial intelligence, 2026)
This article examines innovative approaches to fostering creativity in preschool children through bionics (biomimicry), the practice of drawing inspiration from natural systems, structures, and processes to solve human challenges. Bionics offers a powerful, interdisciplinary framework for early childhood education by encouraging observation of nature, imaginative adaptation, problem-solving, and hands-on exploration. The study synthesizes theoretical foundations from developmental psychology, educational bionics, and biomimicry principles with practical pedagogical strategies suitable for children aged 3–6. It highlights benefits such as enhanced cognitive flexibility, curiosity, collaborative skills, and environmental awareness. Drawing on both international and Uzbek educational literature, the article proposes methodology for implementation, presents hypothetical yet evidence-based results from pilot-like activities, and discusses implications for preschool curricula in Uzbekistan and beyond. Bionics not only nurtures creativity but aligns with play-based learning reforms in Uzbekistan, promoting holistic child development grounded in the wonders of the natural world.